Domain‐General Cognitive Ability Predicts Bilingual Children's Receptive Vocabulary in the Majority Language. Issue 2 (11th January 2019) - Blom, Elma
Abstract: This study investigated the influence of cognitive ability on bilingual children's vocabulary development in both their languages. Sixty‐nine bilingual immigrant children participated, with data collected at three annual intervals. At Time 1, the participants were 5 or 6 years old. Receptive vocabulary was tested in the minority (Turkish, Tarifit) and majority (Dutch) languages. Cognitive measures targeted working memory, selective attention, and executive attention. Cross‐lagged correlations were computed to establish the directionality of relationships. Significant partial correlations were followed by stepwise multiple regression analyses in which further control was exerted. Results showed that cognitive ability predicted receptive vocabulary 1 year later. Sequential relationships were found for the majority language only, and attention was more important than working memory. The differential patterns for the two languages set the stage for future research comparing the impact of context, timing, and type of learning on the relationship between cognition and vocabulary development. Abstract :